A Linear 19-Mer Plant Defensin-Derived Peptide Acts Synergistically with Caspofungin against Candida albicans Biofilms - Cools, Tanne L.; Struyfs, Caroline; Drijfhout, Jan W.; Kucharíková, Soňa; Lobo Romero, Celia; Van Dijck, Patrick; Ramada, Marcelo H. S.; Bloch, Carlos; Cammue, Bruno P. A.; Thevissen, Karin (Frontiers in Microbiology, 2017)
Public health problems are associated with device-associated biofilm infections, with Candida albicans being the major fungal pathogen. We previously identified potent antibiofilm combination treatment in which the antifungal plant defensin HsAFP1 is co-administered with caspofungin, the preferred antimycotic to treat such infections. In this study, we identified the smallest linear HsAFP1-derived peptide that acts synergistically with caspofungin or anidulafungin against C. albicans as HsLin06_18, a 19-mer peptide derived from the C-terminal part of HsAFP1. The [caspofungin + HsLin06_18] combination significantly reduced in vitro biofilm formation of C. glabrata and C. albicans on catheters, as well as biofilm formation of a caspofungin-resistant C. albicans strain. The [caspofungin + HsLin06_18] combination was not cytotoxic and reduced biofilm formation of C. albicans in vivo using a subcutaneous rat catheter model, as compared to control treatment. Mode of action research on the [caspofungin + HsLin06_18] combination pointed to caspofungin-facilitated HsLin06_18 internalization and immediate membrane permeabilization. All these findings point to broad-spectrum antibiofilm activity of a combination of HsLin06_18 and caspofungin.